Impact of Sarcopenia on Falls, Mobility Limitation, and Mortality Using the Diagnostic Criteria Proposed in the Korean Working Group on Sarcopenia Guideline - Ga Yang Shim; Hak Chul Jang; Ki-Woong Kim; Jae-Young Lim (Annals of Geriatric Medicine and Research, 2025)
Background The recent published Korean Working Group on Sarcopenia (KWGS) guideline includes the concept of functional sarcopenia. The study investigated the prevalence of sarcopenia and its association with health-related adverse outcomes defined by the KWGS in community-dwelling older adults. Methods Data were sourced from the Korean Longitudinal Study on Health and Aging, focusing on Koreans 65 aged and above. The definitions of sarcopenia and functional sarcopenia followed the KWGS. The risks of falls, mobility limitation, and death were analyzed using logistic regression and Cox proportional hazard. Results Of the 594 participants, 145 (24.4%) were classified as having functional sarcopenia and 129 (12.0%) with sarcopenia. Both showed an increased prevalence with age. Functional sarcopenia had higher risks of mobility limitation (odds ratio [OR]=3.461; 95% confidence interval [CI], 1.956–6.121) and mortality (hazard ratio [HR]=1.775; 95% CI, 1.229–2.564). Sarcopenia was associated with falls (OR=3.934; 95% CI, 1.327–11.713), mobility limitation (OR=2.057; 95% CI, 1.172–3.611) and mortality (HR=1.512; 95% CI, 1.054–2.169). Conclusion Functional sarcopenia is a prevalent condition that is associated with mobility limitation and mortality in community-dwelling older adults. This highlights the clinical relevance of functional sarcopenia and supports its inclusion in sarcopenia diagnosis.